2016
DOI: 10.1063/1.4968038
|View full text |Cite
|
Sign up to set email alerts
|

Stable isomers and electronic, vibrational, and optical properties of WS2 nano-clusters: A first-principles study

Abstract: In this paper, we employ an evolutionary algorithm along with the full-potential density functional theory (DFT) computations to perform a comprehensive search for the stable structures of stoichiometric (WS) nano-clusters (n = 1 - 9), within three different exchange-correlation functionals. Our results suggest that n = 5 and 8 are possible candidates for the low temperature magic sizes of WS nano-clusters while at temperatures above 500 Kelvin, n = 7 exhibits a comparable relative stability with n = 8. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This results reflects the importance role of transition met-als in determining the stable geometry of TMDCs nanoclusters. We also noticed that, WS 2 nanoclusters exhibit less tendency to planner configurations, because even at larger sizes, WS 2 nanoclusters are not quite planner 60 .…”
Section: A Stable and Metastable Isomersmentioning
confidence: 58%
See 1 more Smart Citation
“…This results reflects the importance role of transition met-als in determining the stable geometry of TMDCs nanoclusters. We also noticed that, WS 2 nanoclusters exhibit less tendency to planner configurations, because even at larger sizes, WS 2 nanoclusters are not quite planner 60 .…”
Section: A Stable and Metastable Isomersmentioning
confidence: 58%
“…It is already observed that nanoclusters of a nonmagnetic material may exhibit magnetism 41,60 . In order to find the stable magnetic state of the clusters, their total energy were minimized by considering different initial magnetization and then the lowest energy state was reported as the stable magnetic state.…”
Section: A Stable and Metastable Isomersmentioning
confidence: 99%
“…It is also noteworthy that we find several structures predicted using an evolutionary algorithm on WS 2 . 23 In addition we found several motifs (Figure 6) shared by many of the stable structures (indicated by colored squares in Figures 2−5): a Mo-centered tetrahedron with S atoms on the edges, a ″core″ of three or four Mo atoms bonded to each other and capped with sulfur atoms, and finally, an S-capped five-membered rings composed of two nonbonded S atoms and three Mo atoms.…”
Section: ■ Resultsmentioning
confidence: 82%
“…Consequently, this has been the focus of a number of experimental 10,11 and theoretical studies. [12][13][14][15][16][17][18][19][20][21][22][23][24]24,25 In some cases, W n S m and W n O m clusters have been studied in parallel with Mo n S m 12,14 due to the chemical similarity between the corresponding metals and chalcogens. Investigating different stoichiometries and cluster sizes provided indeed useful information: so called "magic clusters" seem to indicate a tendency to favor over-saturation in sulfur and monolayer-like structures with growing size, rather than 3D arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation